2003
DOI: 10.1080/00365520310007008
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of gastro‐oesophageal reflux disease: the neglected factor

Abstract: The natural history of gastro-oesophageal reflux disease (GORD) is still a matter for research. The follow-up of GORD patients under placebo and after suspension of the drugs that healed the disease, along with observations of large patient populations treated with, or without, antisecretory drugs for long periods of time, may give some information on the spontaneous evolution of the disease. To single out the outcome of each patient, predictive factors based on demographic, morphologic and pathophysiologic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On average, more acid is refluxed into the esophagus in those presenting with mucosal breaks compared to those without, but great overlap exists 3 . Moreover, it is far from clear whether some GERD patients who initially present with no mucosal breaks, eventually develop these 4,5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, more acid is refluxed into the esophagus in those presenting with mucosal breaks compared to those without, but great overlap exists 3 . Moreover, it is far from clear whether some GERD patients who initially present with no mucosal breaks, eventually develop these 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, it is far from clear whether some GERD patients who initially present with no mucosal breaks, eventually develop these. 4,5 There is a growing interest in histological changes at the region of the squamo-columnar junction (SCJ). 6 The most extensively studied and recognized parameters, believed to represent acid-peptic damage to the epithelium, are: thickening of the basal squamous cell layer (BCL) representing basal cell hyperplasia, increased length of the mucosal papillae (PL) 7 and dilatation of the intercellular spaces (DIS).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent lack of a relationship between extent of esophageal acid exposure time (and other pathophysiologic parameters of reflux and of esophageal motility) and development of esophagitis has been taken into consideration recently [22] , and it has been suggested that the majority of investigations conducted so far have overlooked the resistance of the esophageal mucosa. Although the effect of smoking on GERD symptoms and lesions is not clear-cut, it probably acts on different pathogenetic sites, including mucosal resistance.…”
Section: Discussionmentioning
confidence: 99%